Resistance and resilience to droughts: hydropedological controls on catchment storage and run‐off response. Issue 21 (1st April 2015) - Geris, Josie; Tetzlaff, Doerthe; Soulsby, Chris; Lin, Henry; McDonnell, Jeffrey; Nimmo, John; Pachepsky, Yakov
Abstract Hydropedological units are of critical importance in modulating catchment response in terms of storage and flux dynamics under changing hydrological conditions. We examined the short‐term impacts of an extreme drought on the storage dynamics and run‐off response in hydropedological units in a headwater catchment in the Scottish Highlands. These included poorly drained histosols in riparian zones and freely draining podzols on steeper hillslopes. To characterize the storage and run‐off dynamics prior to, during and after the drought period, precipitation, soil moisture, shallow ground water levels and consequent run‐off were monitored and stable water isotopes samples collected. Storage changes in the histosols were remarkably small (<40 mm), compared with those in moorland (~100 mm) and forest (~200 mm) covered podzols. Although storage in all soils recovered soon after the drought, this took longest (3–4 months) for the forested podzols. During events, there was consistent threshold behaviour in most hydropedological units and the integrated response at the catchment scale, which was not affected by drying or wetting. The results suggest that during dry periods, large parts of the catchment were disconnected from the river network and run‐off was generated mainly from the wet histosols. However, during events, there was an intermittent connection of the hillslopes that recharged the wetland and stream. This contributed to strong recovery and resilience of the catchment in its run‐off response. Nevertheless, as future climate projections for northern environments suggest that prolonged dry periods are likely to become more frequent, further work is needed on the potential cumulative or carry over effects of consecutive drier periods. Copyright © 2015 John Wiley & Sons, Ltd.